Development of village website and hot spring water quality evaluation for sustainable tourism empowerment in Sumberarum Village, Magelang - Lintang Muliawanti; Zulfikar Bagus Pambuko; Fitriana Yuliastuti; Missya Putri Kurnia Pradani (Community Empowerment, 2024)
Sumberarum Village, Magelang Regency, holds great tourism potential with its natural hot springs, which remain underutilized. The main challenges include the lack of integrated digital information and limited digital marketing skills among the local community. This community service initiative aims to develop sustainable tourism potential through the creation of a village website and the evaluation of hot spring water quality. The approach includes developing a village website at desasumberarum.id as a centralized tourism information hub and measuring water quality parameters at four hot spring locations: Umbul Banyu Roso, Tirta Madu Barokah, Tirta Sambara, and Azzira Tirta Gemilang. Results indicate that the village website significantly improves information accessibility and supports digital tourism promotion. Additionally, water quality tests reveal that all parameters, including pH and alkalinity, fall within safe thresholds, suggesting potential health benefits of the hot spring water for visitors.